ANALISIS PENGARUH KUALITAS WEBSITE DAN INFORMASI, ONLINE TRUST, SERTA SALES PROMOTION TERHADAP MINAT BELI ULANG DENGAN CUSTOMER EXPERIENCE SEBAGAI VARIABEL INTERVENING (STUDI PADA PELANGGAN E-COMMERCE ELEVENIA DI KOTA SEMARANG) - Samudro, Naval; Ferdinand, Augusty Tae (Diponegoro Journal of Management, 2019)
Customers repurchase intention is a crucial factor and determines how an e-commerce maintaining the customer in the middle of the e-commerce competition, so the company must be able to maintain and improve the factors that affect customers repurchase intention to gain the interest of customers in the middle of the e-commerce competition in IndonesiaThis research used an e-commerce startup Elevenia as the research object. The purpose of this research is to examine how the website and information quality, online trust and sales promotion influence repurchase intention by using the online customer experience as an intervening variable. The samples was collected by distributing questionnaires to 100 respondents who has an online purchasing experience at Elevenia and resided in the city of Semarangwhich were then analyzed using multiple linear regression methods with the tests carried out, validity test, reliability test, classic assumption test, coefficient of determination test, F test, test T, and the sobel test to find out the mediating effect.The results of this research showed that the website and information quality have a positive and significant effect on online customer experience), then online trust and sales promotion have a significant and positive influence on repurchase intention, and the results of the test of sobel showed, the online customer experience worthy to be used as an intervening variable.